Lipopolysaccharide enhances TGF‐β1 signalling pathway and rat pancreatic fibrosis. Issue 4 (9th February 2018) - Sun, Li; Xiu, Ming; Wang, Shuhua; Brigstock, David R.; Li, Hongyan; Qu, Limei; Gao, Runping
Abstract: Pancreatic stellate cells (PSCs) play a critical role in fibrogenesis during alcoholic chronic pancreatitis (ACP). Transforming growth factor‐beta1 (TGF‐β1) is a key regulator of extracellular matrix production and PSC activation. Endotoxin lipopolysaccharide (LPS) has been recognized as a trigger factor in the pathogenesis of ACP. This study aimed to investigate the mechanisms by which LPS modulates TGF‐β1 signalling and pancreatic fibrosis. Sprague‐Dawley rats fed with a Lieber‐DeCarli alcohol (ALC) liquid diet for 10 weeks with or without LPS challenge during the last 3 weeks. In vitro studies were performed using rat macrophages (Mφs) and PSCs (RP‐2 cell line). The results showed that repeated LPS challenge resulted in significantly more collagen production and PSC activation compared to rats fed with ALC alone. LPS administration caused overexpression of pancreatic TLR4 or TGF‐β1 which was paralleled by an increased number of TLR4‐positive or TGF‐β1‐positive Mφs or PSCs in ALC‐fed rats. In vitro, TLR4 or TGF‐β1 production in Mφs or RP‐2 cells was up‐regulated by LPS. LPS alone or in combination with TGF‐β1 significantly increased type I collagen and α‐SMA production and Smad2 and 3 phosphorylation in serum‐starved RP‐2 cells. TGF‐β pseudoreceptor BAMBI production was repressed by LPS, which was antagonized by Si‐TLR4 RNA or by inhibitors of MyD88/NF‐kB. Additionally, knockdown of Bambi with Si‐Bambi RNA significantly increased TGF‐β1 signalling in RP‐2 cells. These findings indicate that LPS increases TGF‐β1 production through paracrine and autocrine mechanisms and that LPS enhances TGF‐β1 signalling in PSCs by repressing BAMBI via TLR4/MyD88/NF‐kB activation.